PENGEMBANGAN LABORATORIUM MIPA IAIN AMBON UNTUK MENDUKUNG PROGRAM MERDEKA BELAJAR KAMPUS MERDEKA - Warandi, Jamal Hasan (AMAL: Jurnal Ekonomi Syariah, 2022)
ABSTRACTThis paper is motivated by the problems found at the Mathematics and Natural Sciences Laboratory (MIPA) of IAIN Ambon in the implementation of the Merdeka Learning Campus Merdeka (MBKM) program related to preparation for implementation, inadequate equipment and budget constraints. The purpose of writing is to design the development of the Ambon IAIN MIPA Laboratory to support the MBKM Program and provide policy recommendations for the development of the Ambon IAIN MIPA Laboratory. The research location that became the locus was the MIPA Laboratory of IAIN Ambon with the nature of exploratory qualitative research. Data collection techniques were carried out in the form of literature studies including from several books, journals, online articles. Analysis of the problems being faced and discussion of alternative development policies required using domain analysis. The results of the analysis of the development of the Ambon IAIN MIPA Laboratory must be upgraded from a Type II Laboratory (Basic Science Laboratory) to a Type IV Laboratory (Integrated Laboratory). Recommendations include the facilities and infrastructure of the Ambon IAIN MIPA Laboratory which still need to be improved by adding laboratory buildings/rooms and category 3 laboratory equipment (equipment that is difficult to operate and maintain, has high risk of use, high accuracy of measurement accuracy, complicated operation and requires special training and certificate laboratory assistants). The total budget and human resources of the Ambon IAIN MIPA Laboratory need to be increased through institutional cooperation and the recruitment of professional functional experts.Keywords: development, laboratory, program ABSTRAKTulisan ini dilatarbelakangi oleh permasalahan yang ditemukan pada Laboratorium Matematika dan Ilmu Pengetahuan Alam (MIPA) IAIN Ambon dalam pelaksanaan program Merdeka Belajar Kampus Merdeka (MBKM) terkait persiapan pelaksanaan, peralatan yang belum memadai serta keterbatasan anggaran. Tujuan penulisan adalah mendesain pengembangan Laboratorium MIPA IAIN Ambon untuk mendukung Program MBKM dan memberikan rekomendasi kebijakan untuk pengembangan Laboratorium MIPA IAIN Ambon. Lokasi penelitian yang menjadi locus yaitu Laboratorium MIPA IAIN Ambon dengan sifat penelitian kualitatif  eksplorasi. Teknik pengumpulan data yang dilakukan berupa studi literatur diantaranya dari beberapa buku, jurnal, artikel online. Analisis terhadap permasalahan yang sedang dihadapi dan pembahasan atas alternatif kebijakan pengembangan yang diperlukan menggunakan analisis domain. Hasil analisis pengembangan Laboratorium MIPA IAIN Ambon harus ditingkatkan dari Laboratorium Tipe II (Laboratorium Ilmu Dasar) menjadi Laboratorium Tipe IV (Laboratorium Terpadu). Rekomendasi diantaranya sarana dan prasarana Laboratorium MIPA IAIN Ambon masih harus dibenahi dengan penambahan gedung/ruang laboratorium serta peralatan laboratorium kategori 3 (peralatan yang pengoperasian dan perawatannya sulit, risiko penggunaan tinggi, akurasi kecermatan pengukuran tinggi, pengoperasian rumit serta perlu pelatihan khusus dan laboran sertifikat). Jumlah anggaran dan sumber daya manusia Laboratorium MIPA IAIN Ambon perlu ditingkatkan melalui kerjasama kelembagaan dan perekrutan tenaga ahli fungsional yang profesional.Kata Kunci: pengembangan, laboratorium, program